ECO-FRIENDLY PEST MANAGEMENT: COMPARING THE EFFICACY OF NEEM AND CEDAR WOOD OILS ON CALLOSOBRUCHUS CHINENSIS L - Sharma, S. (International Journal of Allied Sciences (IJAS), 2022)
This study aimed to compare the fumigant potential and ovipositional behavior of neem oil, Himalayan cedar wood oil, and their combination against the pulse beetle, Callosobruchus chinensis L. The cedar wood oil was found to exhibit the highest knock-down effect of up to 100% at 3% concentration, while neem oil demonstrated the least corrected % knock-down. The mortality rate was highest in cedar wood oil rather than neem oil and their combination. However, the combined treatment of neem oil and cedar wood oil at 3% concentration exhibited a mortality rate comparable to cedar wood oil 3% concentration. In an ovipositional behavioral experiment, cedar wood oil-treated chickpea grains had the highest mean number of eggs laid per 5 females compared to neem oil-treated grains. This study suggests the joint action potential of Himalayan cedar wood oil with neem oil and its possible use in the formulation of botanical insecticides. The utilization of naturally occurring sources of pesticides becomes essential due to the lack of quick biodegradability of synthetic pesticides, leading to the accumulation of residues, development of insect resistance, and destruction of beneficial arthropods and aquatic animals.